Repair of Isoaspartate Formation Modulates the Interaction of Deamidated 4E-BP2 with mTORC1 in Brain - Bidinosti, Michael (American Society for Biochemistry and Molecular Biology, 2010)
In eukaryotes, a rate-limiting step of translation initiation is recognition of the mRNA 5′ m(7)GpppN cap structure by the eukaryotic initiation factor 4F (eIF4F), a heterotrimeric complex consisting of the cap-binding protein, eIF4E, along with eIF4G, and eIF4A. The eIF4E-binding proteins (4E-BPs) repress translation by disrupting eIF4F formation, thereby preventing ribosome recruitment to the mRNA. Of the three 4E-BPs, 4E-BP2 is the predominant paralog expressed in the mammalian brain and plays an important role in synaptic plasticity and learning and memory. 4E-BP2 undergoes asparagine deamidation, solely in the brain, during early postnatal development. Deamidation spontaneously converts asparagines into a mixture of aspartates or isoaspartates, the latter of which may be destabilizing to proteins. The enzyme protein l-isoaspartyl methyltransferase (PIMT) prevents isoaspartate accumulation by catalyzing the conversion of isoaspartates to aspartates. PIMT exhibits high activity in the brain, relative to other tissues. We report here that 4E-BP2 is a substrate for PIMT. In vitro deamidated 4E-BP2 accrues isoapartyl residues and is methylated by recombinant PIMT. Using an antibody that recognizes 4E-BP2, which harbors isoaspartates at the deamidation sites, Asn(99) and Asn(102), we demonstrate that 4E-BP2 in PIMT−/− brain lysates contains isoaspartate residues. Further, we show that 4E-BP2 containing isoaspartates lacks the augmented association with raptor that is a feature of deamidated 4E-BP2.